Examine the influence of Enterprise Resource Planning Quality Dimensions on Organizational Performance Mediated through Business Process Change Capability (Global Business Management Review (GBMR), 2020)
This study examines the influence of enterprise resource planning (ERP) quality dimensions on organizational performance using the theoretical lens of dynamic capability theory by taking business process change capability as a mediator in the relationship of ERP system quality dimensions and Organizational Performance. Respondents were information technology (IT) managers from firms using ERP system in Pakistan. Statistical analysis was carried using variance based partial least square (PLS) method. The results revealed the business process change capability mediates the relationship between ERP quality dimensions and organizational performance. This research provides practical as well as theoretical implications by highlighting the business change capabilities in translating ERP system quality into enhanced organizational performance.